2017
DOI: 10.1111/apt.14290
|View full text |Cite
|
Sign up to set email alerts
|

Food elimination diets are effective for long‐term treatment of adults with eosinophilic oesophagitis

Abstract: Summary Background Limited data describe the long-term efficacy of dietary elimination in eosinophilic oesophagitis (EoE). Aim We assessed the long-term outcomes of food elimination diets (FED) for treatment of adults with EoE. Methods We conducted a retrospective cohort study at our center analyzing all EoE patients receiving a FED without concomitant steroids. Baseline data were abstracted using standardized collection forms. Follow-up data from a mean 24.9-month period were collected for patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 40 publications
0
48
0
3
Order By: Relevance
“…The effective therapies available to adults with EoE are numerous . We hypothesise that similar to other chronic conditions, knowledge of EoE patients’ expectations towards therapy in conjunction with, among others, adequate health literacy, and good physician‐patient partnership may lead to better decisions about the choice of therapy and reduce nonadherence .…”
Section: Discussionmentioning
confidence: 99%
“…The effective therapies available to adults with EoE are numerous . We hypothesise that similar to other chronic conditions, knowledge of EoE patients’ expectations towards therapy in conjunction with, among others, adequate health literacy, and good physician‐patient partnership may lead to better decisions about the choice of therapy and reduce nonadherence .…”
Section: Discussionmentioning
confidence: 99%
“…Among studies that examined the effectiveness of monoclonal antibody treatment in EoE subjects, 80% defined histological remission as peak esophageal eosinophil counts within the range of 0 to ≤5 24, 25, 26, 27, 28. Approximately 26% (N = 15) of the eligible studies examined remission among EoE patients who received only the diet elimination treatment formula (SFED, FFGED, ELED) compared to other forms of treatment, with the most common definitions falling within 0 to ≤5 eosinophils/hpf 29, 30, 31, 32, 33, 34 or 11 to ≤15 eosinophils/hpf 35, 36, 37, 38, 39, 40. Interestingly, even among the SFED studies (N = 9), five studies defined remission within the range of 0 to ≤5 eosinophils/hpf, 29, 30, 31, 32, 34 and two studies considered histological remission as <15 eosinophils/hpf 38, 41…”
Section: Resultsmentioning
confidence: 99%
“…diet elimination or restriction), we observed that medication trial studies (e.g. steroids, monoclonal antibody) used more rigorous criteria in their definition of histological remission in study subjects with EoE 21, 26, 27, 35, 53, 60. It is possible that different cut‐off values of peak eosinophil counts per hpf are appropriate for the definition of histological improvement because of the variations in the trial methodology (treatment, subjects’ characteristics).…”
Section: Discussionmentioning
confidence: 99%
“…9 As more patients are being treated with dietary intervention, further evidence regarding long-term outcomes is awaited. One recent study found that in patients who were able to adhere, dietary elimination remained effective, but over half of patients relapsed due to compliance or iatrogenic food reintroduction.…”
Section: Discussionmentioning
confidence: 99%